2008
DOI: 10.1038/gene.2008.74
|View full text |Cite
|
Sign up to set email alerts
|

Conditional analyses on the T1DGC MHC dataset: novel associations with type 1 diabetes around HLA-G and confirmation of HLA-B

Abstract: The major histocompatibility complex (MHC) is known to harbour genetic risk factors for type 1 diabetes (T1D) additional to the class II determinants HLA-DRB1, -DQA1 and -DQB1, but strong linkage disequilibrium (LD) has made efforts to establish their location difficult. This study utilizes a dataset generated by the T1D genetics consortium (T1DGC), with genotypes for 2965 markers across the MHC in 2321 T1D families of multiple (mostly Caucasian) ethnicities. Using a comprehensive approach consisting of comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 61 publications
5
44
0
Order By: Relevance
“…One of the BTN3A2 SNPs, rs13218591, lost its borderline association when either the HLA-A or -B locus was included in the main effects test, whereas the other, rs11758089, remained significant after inclusion of either of the HLA class I loci. Furthermore, in the earlier T1DGC screen we have also reported association with SNPs near HLA-G, that is, rs4122198, rs1619379 and rs2394186, 25 and others have reported association with SNPs in the UBD/MAS1L region (particularly with rs1233478). 24 When conditioning on each of these SNPs (together with DRB1-DQA1-DQB1 and HLA-B), the association with the SNPs in the extended class I region remained significant and vise versa, except for the PRSS16 SNP rs9393796 when adjusting for rs2394186 (data not shown).…”
Section: Resultsmentioning
confidence: 57%
See 4 more Smart Citations
“…One of the BTN3A2 SNPs, rs13218591, lost its borderline association when either the HLA-A or -B locus was included in the main effects test, whereas the other, rs11758089, remained significant after inclusion of either of the HLA class I loci. Furthermore, in the earlier T1DGC screen we have also reported association with SNPs near HLA-G, that is, rs4122198, rs1619379 and rs2394186, 25 and others have reported association with SNPs in the UBD/MAS1L region (particularly with rs1233478). 24 When conditioning on each of these SNPs (together with DRB1-DQA1-DQB1 and HLA-B), the association with the SNPs in the extended class I region remained significant and vise versa, except for the PRSS16 SNP rs9393796 when adjusting for rs2394186 (data not shown).…”
Section: Resultsmentioning
confidence: 57%
“…9 Furthermore, it indicates that our susceptibility locus maps away from the classical MHC, although additional risk loci are also believed to exist there, in particular for HLA-B. 25,[27][28][29] It is interesting to note that conditional logistic regression analyses in the T1DGC dataset showed that the associations with the PRSS16 SNPs and one of the BTN SNPs were independent of HLA-B, and also of the other class I loci. The associations with the PRSS16 SNPs also seemed independent of the earlier reported UBD and HLA-G associations, though some dependency was seen in the regression analyses between one of the HLA-G SNPs and one of the PRSS16 SNPs, even though there was hardly any LD between these SNPs when calculated on the basis of the entire T1DGC dataset.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations